PENGARUH FATIGUE TERHADAP KINERJA PERSONEL AIR TRAFFIC CONTROLLER DI UNIT AERODROME CONTROL TOWER JAKARTA AIR TRAFFIC SERVICE CENTER (JATSC) - Annisa Fitri; Rini Sadiatmi; Endang Sugih Arti (Politeknik Penerbangan Indonesia Curug, 2019)
Jakarta Air Traffic Service Center (JATSC) is one of the air traffic service centers in Indonesia which handles the densest air space in Indonesia. JATSC is the center of air traffic control in the western airspace of Indonesia and oversees the other airspace. Increasing the amount of traffic will increase the workload of air traffic guides in providing air traffic services. Increased workload can affect the physical condition of an air traffic guide which allows human error to occur. One of the human factors that can reduce the performance of ATC in making decisions is fatigue. The study concluded that there is a negative relationship between fatigue and performance with a correlation coefficient of (-) 0.650 and a coefficient of determination of 42% means that fatigue has a strong and significant effect on the performance of ATC personnel and the rest is influenced by other factors. Steps that can be taken to prevent and reduce the risk of fatigue are the need for special attention to the preparation of official schedules and special training on Fatigue Risk Management System (FRMS) on meditation and relaxation that is expected to be applied in everyday life